(untitled) (Al-Academy, 2024)
In the midst of conflicts different intellectual and knowledge of production processes and circulation we need constant search for different levels of Innovation replenished with renewed need to develop solutions to various problems. Amid this conflict comes to mind a question about what salt creative mechanisms act in Graphic Design? Through this research is marked (creative mechanisms act in Graphic Design) strive to find solutions to this question, as well as cognitive it Sarphi side modern and developmental study to a broader understanding of the subject. And across four seasons, which included the first chapter of the research problem and the need for him, and then came the second chapter includes theoretical framework goal Bembgesan, came First research titled (creativity in art and theories creative) and the second section (thinking and mechanism of action creative in Graphic Design) and then right indicators represent Summary scientific literature Article theoretical, in the third quarter set the research methodology and Tgosailadtha technical, and the right process analysis to design commercials printed magazines foreign available in the local market and adopted researcher indicators theoretical framework as the research sample was selected in the manner of others Probability intentionality by the nature of research has been on the basis of analysis sample models. fourth chapter and which contained the results of research and discussion, from these results:1 - The idea indirect characterized creativity as a result of the formulation of the new formalism as it led to the excitement, excellence and attractions, as well as to raise the intellectual implications.2 - The employment picture processing technicians to achieve formal Allamolov the advertised product led to the realization of the idea of creative and play Atsalaa by delivering advertising idea in an interesting and strange.3 - has been the application of environmental metaphors and formal and synthesized with elements used in advertising design to achieve artistic creativity. Then I pointed out the recommendations and proposals and a list of the sources cited by the research.